2015
DOI: 10.1111/fcre.12135
|View full text |Cite
|
Sign up to set email alerts
|

Does Level of Intimate Partner Violence and Abuse Predict the Content of Family Mediation Agreements?

Abstract: This study investigated whether reported levels of intimate partner violence (IPV) and/or abuse (IPV/A) victimization are related to reaching agreement and to the content of mediation agreements of parties seeking to resolve family‐ and child‐related issues. Whether or not parties reached agreement was analyzed for 105 cases at a law school mediation clinic. Agreement content was coded for the 71 cases that reached agreement. Levels of IPV and IPV/A were determined separately for males and females, using a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 20 publications
0
31
2
Order By: Relevance
“…While the studies of Beck et al () and Rossi et al () are very meaningful, their studies are different than ours in important ways. These two studies rank ordered IPV cases from least to most severe IPV.…”
Section: Literature Reviewcontrasting
confidence: 76%
See 4 more Smart Citations
“…While the studies of Beck et al () and Rossi et al () are very meaningful, their studies are different than ours in important ways. These two studies rank ordered IPV cases from least to most severe IPV.…”
Section: Literature Reviewcontrasting
confidence: 76%
“…Similarly, Ballard et al () argues that IPV is a significant predictor of agreement because couples without IPV showed a 2.8 times higher possibility of reaching full agreement than couples with IPV. Rossi et al () found an interesting result; males reporting higher levels of IPV/A predicted lower settlement rates. According to Rossi et al (), this result may imply that male victims feel sufficiently empowered to discuss their interests and that they have to reach an agreement in mediation.…”
Section: Literature Reviewmentioning
confidence: 95%
See 3 more Smart Citations